2022
DOI: 10.1177/10732748221091333
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Values of the Selected Inflammatory Indexes in Colon Cancer

Abstract: Purpose Ample evidence has revealed that the lymphocyte-to-monocyte ratio (LMR), albumin-to-globulin ratio (AGR), and mean platelet volume (MPV) are cancer-related inflammatory markers. The present study aimed to combine these indicators to better assess the progression of colon cancer. Methods This retrospective study enrolled 251 patients with colon cancer, 171 patients with benign colon diseases, and 187 healthy control subjects. The receiver operating characteristic curve and area under the curve (AUC) wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 53 publications
1
10
0
Order By: Relevance
“…Regarding colon cancer, eleven studies were identified [ 13 , 19 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ] including 3463 patients with colon cancer or colorectal cancer ( Table 2 ). Seven studies were conducted in China [ 19 , 38 , 39 , 41 , 43 , 45 , 46 ], two in Turkey [ 40 , 42 ], one in Serbia [ 13 ], and one in Qatar [ 44 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Regarding colon cancer, eleven studies were identified [ 13 , 19 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ] including 3463 patients with colon cancer or colorectal cancer ( Table 2 ). Seven studies were conducted in China [ 19 , 38 , 39 , 41 , 43 , 45 , 46 ], two in Turkey [ 40 , 42 ], one in Serbia [ 13 ], and one in Qatar [ 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…Regarding colon cancer, eleven studies were identified [ 13 , 19 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ] including 3463 patients with colon cancer or colorectal cancer ( Table 2 ). Seven studies were conducted in China [ 19 , 38 , 39 , 41 , 43 , 45 , 46 ], two in Turkey [ 40 , 42 ], one in Serbia [ 13 ], and one in Qatar [ 44 ]. Results were mixed regarding the values of MPV in patients versus controls, with one study showing increased MPV in patients with colon cancer [ 39 ] and one showing decreased MPV levels [ 45 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations